The Impact of Trump Administration Tariffs on Global Trade and Commodity Prices - Angwaomaodoko, Ejuchegahi A. (Theoretical and Practical Research in Economic Fields, 2025)
This current research evaluates the impact of Trump-era tariffs on the trends of global trade and commodity prices, with specific focus on the overall implications of U.S. protectionist trade policy. Utilizing a multi-sector methodology, the research takes into account the implications of key tariff measures taken under Sections 232 and 301 of U.S. trade legislation, particularly those directed against steel, aluminium, and a broad range of Chinese imports. The article explores how these tariffs affected two-way trade flows - especially between the U.S. and China - and caused dramatic shifts in global supply chains, with production diverted more and more to countries like Vietnam and Mexico. The study also examines the sectoral impact on commodities, highlighting how U.S. agricultural exports such as soybeans and pork dropped due to Chinese retaliation, while metal and energy markets were affected by price volatility, supply chain congestion, and strategic restructuring. Results indicate that although the tariffs were intended to increase domestic production and restore trade deficits, they led to unintended consequences such as higher U.S. importers' expenses, reduced export competitiveness, and further uncertainty in commodity markets. The study concludes by indicating the long-term economic implications of trade wars on worldwide economic stability as well as the necessity of multilateral approaches to trade reform.